EFFECT OF OPTIMIZATION OF TWEEN 80 AND PROPYLENE GLYCOL AS A SURFACTANT AND COSURFACTANT ON THE PHYSICAL PROPERTIES OF ASPIRIN MICROEMULSION - Yati, Kori; Srifiana, Yudi; Putra, Farensyah (International Journal of Applied Pharmaceutics, 2017)
Background: Aspirin is recommended as a first-line antiplatelet drug for all types of acute diseases that cause thrombosis in the blood vessel, especially in cardiovascular disease. Orally administered aspirin has side effects such as the risk of gastrointestinal bleeding and has presystemic metabolism in the gastrointestinal tract and liver. Transdermal delivery offers an alternative for administering aspirin that by passes the gut and this may be more convenient and safe for long-term use. This study used a form of microemulsion to prevent hydrolysis of aspirin because it contains a high concentration of the surfactant. A microemulsion is a dosage form that can penetrate into the skin for transdermal delivery. Objectives: The aim of this research was to evaluate the effect of Tween 80 and propylene glycol as the surfactant and cosurfactant on the physical stability of the microemulsion. Materials and Methods: Various concentrations of Tween 80 and propylene glycol (2:1) were used 54%, 57%, 60%, and 63%, and the physical stability of the different microemulsions was tested for 6 weeks. Result: The results showed that the formula F3 was the most stable formula. The formula F3 showed the following properties such as pH of 3.74±0.30, viscosity of 1198.76±56.02 cps, BJ of 1.0669±0.005 g/mL, surface tension of 38.77±0.43 dyne/cm, and particle size of 49.46±6.91 nm. Conclusions: Based on the results concluded that the optimum concentration of Tween 80 as the surfactant and propylene glycol as the cosurfactant with a ratio of 2:1 was 60%.